TI_GERICHTE 52.2020.197 vom 13. März 2020 , Ordine di sospensione di un'attività non autorizzata. Divieto d'uso - TI Tribunale d'appello (2020)
Ordine di sospensione di un'attività non autorizzata. Divieto d'uso